Development of potential immunodiagnostic & therapeutic techniques using SNAP-fusion proteins as tools for the validation of Triple-negative Breast Cancer - Magugu, Freddy-Junior Siybaulela (Department of Integrative Biomedical Sciences (IBMS), 2021)
Globally, breast cancer is the leading cause of death in the female population aged 45 and below with a breast cancer incidence reaching 18.1 million in the year 2018. Triple negative breast cancer (TNBC) is part of a group of cancers that lack the expression of Progesterone receptor (PR), Estrogen receptor (ER) and Human epidermal growth factor receptor 2 (HER2). TNBC is commonly associated with early stage metastasis with low survival rates as well as a high frequency of recurrence and proves to be problematic in both the young and elderly female populations. Conventional diagnostic methods for TNBCs include mammography, magnetic resonance imaging (MRI) and ultrasound while therapeutic methods include mastectomy and breast conserving surgery (coupled with radiation therapy). The lack of effective therapeutic options, poor prognostic value and high rates of metastasis, has made treatment of TNBC difficult. The major focus of this work was on the following tumour associated antigens (TAAs): CSPG4 (a transmembrane protein found in 50% of TNBC cases), EGFR (which is overexpressed in 13-76% of TNBCs), and MSLN (which is overexpressed in 67% of TNBCs) as potential targets for monospecific therapy. The evolution of antibody-based immunotherapy strategies has led to applications of single chain variable fragment (scFv) & single domain/nanobody (VHH) antibody formats for diagnostic and therapeutic purposes. In this work, these recombinant antibody fragments have been combined with SNAP-tag, a modified version of the human DNA repair enzyme O6-alkylguanine-DNA-alkyltransferase (AGT), which autocatalytically binds benzyl-guanine modified substrates such as fluorophores or small molecule toxins covalently in a 1:1 stoichiometry. In this study, the primary aim was the comparison of different antibody formats fused to SNAPtag and the potential of these biopharmaceuticals towards immunodiagnosis and therapy of TNBCs. First functionalities of two scFv SNAP fusion proteins and one VHH SNAP fusion protein previously not having been described are provided through binding analyses on receptor positive tumour cell lines. This was achieved by in-silico design and molecular cloning of genetically fused antiCSPG4(scFv), -MSLN(scFv), -MSLN(VHH), -EGFR(scFv) & -EGFR(VHH) to SNAP-tag. The final constructs were confirmed by Sanger sequencing and subsequently transfected into a mammalian vector system (HEK293T) for transient expression of the engineered fusion proteins. Full length protein purified from cell culture supernatant was analysed for diagnostic/therapeutic activities dependant on the substrate attached in the form of a fluorophore or small molecule toxin resulting in recombinant antibody-drug conjugates (ADCs). The study shows promise in providing new immunodiagnostic and therapeutic agents that are specific and less harmful than the current state of the art procedure